Multimodal signaling in Boana albopunctata (Anura: Hylidae): reading visual and acoustic cues - Lourenco, Andrea Rosel de; Haddad, Celio F. B.; Sa, Fabio P. de [UNESP] (Univ Sao Paulo, Esalq, 2020)
The acoustic mode of communication is important for anurans, but visual communication is beginning to be considered essential for some species, genera, and families. This study focuses on visual and acoustic signals in Boana albopunctata (Hylidae: Cophomantinae) in an attempt to increase our understanding of signaling in this nocturnal Neotropical treefrog. Visual signals were assessed to determine whether they are directed toward conspecific opponents, as has already been observed for some diurnal anurans, or associated with potential morphological asymmetries. Associations between visual and acoustic signals were explored. The results suggest that males may combine visual and acoustic signals (multimodal signaling) synergistically, thereby strengthening the efficiency of information transmission. Thus, in nocturnal anuran species, visual signals may function primarily as an alerting component and multimodal signaling may be a relevant way of communication.
Keywords: alerting function; territoriality; visual signaling